Enhancing mathematical understanding through real objects: Insights from Tanzanian classrooms - Deogratias, Emmanuel; Ngonyani, Christer; Gadala, Yoram (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This research investigates the use of real objects and improvisation as learning aids by mathematics teachers in secondary schools within Morogoro Municipality. The study employed a quantitative approach, involving 101 mathematics teachers, to assess the effectiveness of real objects and improvisation in enhancing students' understanding of mathematical concepts. Using a case study research design, the study targeted mathematics teachers in secondary schools in Morogoro Municipality, selected through purposive and convenience sampling. The findings reveal that real objects and improvisation have great potential in enhancing students’ understanding of mathematical concepts. Real objects can be effectively used to reinforce students’ comprehension of mathematics during classroom instruction. They also facilitate easier understanding of mathematical concepts, such as perimeter and area. Additionally, real objects promote student engagement in learning mathematics during lesson delivery and help students bridge the gap between theory and practice. These findings have significant implications for the teaching and learning of mathematics, as they indicate that students become more actively engaged with mathematical concepts, while teachers improve their pedagogical practices in secondary school settings. This study recommends the use of real objects in mathematics classrooms to increase student participation, relate mathematical concepts to students’ daily experiences, and enhance learning outcomes.